A semiotic analysis of the male gaze in ?Darna? (2022) - Daliling, Veda Sachi C.
The Philippine film industry has long faced the incessant issue of the ?male gaze,? a term first coined by Laura Mulvey in 1973. This thesis examines the male gaze in ?Darna? (2022) using semiotic analysis. The main objectives of this study are: (1) Identify elements that cater to or subvert the male gaze in the semiotic signs of ?Darna? (2022), (2) Describe the portrayal of female characters in ?Darna? (2022) and analyze its meaning in relation to the male gaze, and (3) Critically explore whether having women in production roles affect the portrayal of female characters regarding the male gaze. Using the orders of signification by Roland Barthes, the male gaze theory by Laura Mulvey, and Visual Methodologies by Gillian Rose to examine the gathered data, the study found three themes under the signs that cater to the male gaze: (1) To-be-looked-at-ness:? Objectification of Female Characters, (2) Reinforcement of Stereotypes, and (3) Camera Perspectives that Objectify Female Characters, and two themes under the signs that subvert the male gaze: (1) Female Activity and Agency, and (2) Complex and Nuanced Characterization of Female Characters. The narrative of ?Darna? (2022), the component of the series in which the female writers are involved, contains all the identified signs that subvert the male gaze. This supports Laura Mulvey's claim that the male gaze can be subverted by having more women in production roles to present female perspectives. Thus, the presence of women in production roles as writers subverted the male gaze in ?Darna? (2022).